New measurement system based on small‐angle neutron scattering for structural analysis of light‐responsive materials. Issue 1 (23rd December 2022) - Iwase, Hiroki; Akamatsu, Masaaki; Inamura, Yasuhiro; Sakaguchi, Yoshifumi; Morikawa, Toshiaki; Kasai, Satoshi; Oh-uchi, Keiichi; Kobayashi, Kazuki; Sakai, Hideki
Abstract : A system has been developed for in situ observation of light‐induced structural changes in materials via small‐angle neutron scattering (SANS). A simultaneous SANS and UV absorption measurement was employed. The result showed that the newly developed system is very useful for analyzing the structure–function relationship of light‐responsive materials. Abstract : With the increasing importance of light‐responsive materials, it is vital to analyze the relationship between function and structural changes induced by light irradiation. Small‐angle scattering (SAS) is effective for such structural analysis. However, quantitatively capturing local molecular structure formation and molecular reactions at a scale of less than 1 nm via SAS is difficult. In this study, to analyze the structure of non‐equilibrium phenomena in light‐responsive materials, a new sample environment has been developed for a time‐of‐flight small‐ and wide‐angle neutron scattering instrument (TAIKAN), comprising a UV–Vis irradiation system, UV–Vis absorption measurement equipment and photodetector. Simultaneous measurement of small‐angle neutron scattering and UV–Vis absorption was achieved. This system was used to demonstrate the in situ observation of UV–Vis irradiation‐induced structural change of micelles formed by 4‐butylazobenzene‐4′‐(oxyethyl)trimethylammonium bromide, which is a light‐responsive surfactant, in an aqueous solution. The results showed that the present measuring system provides direct information on the interplay between changes in micelle structure and changes in molecular configuration.